The International Criminal Court and the prosecution of sitting heads of state: democracy, enforcement, and symbolism of a revolutionary practice in international politics - Cacciatori, Mattia (Palgrave Macmillan, 2024)
The practice of prosecuting sitting Heads of State (SHoS) by the International Criminal Court (ICC) represents a revolutionary and morally compelling pursuit of justice for those who commit the most heinous crimes known to humanity, regardless of their status. This book embarks on an exploration of the intricate political dynamics surrounding this complex practice, delving into six pivotal cases where the ICC grappled with the idea of prosecuting SHoS. These cases encompass Uganda, Sudan, Kenya, Libya, Syria, and Russia, encompassing all instances where the ICC directly targeted SHoS, as well as two cases where the Court was unable or unwilling to act. The investigation focuses on the multifaceted political complexities involved in initiating investigations against sitting Heads of State. It also delves into the far-reaching domestic and international consequences these prosecutions carried, profoundly impacting both the host societies and the international arena. Dr. Mattia Cacciatori, a Lecturer in International Relations and International Security at the University of Bath, specializes in international law's impact on conflict resolution, prosecuting sitting Heads of State, and assessing the effectiveness of transitional justice mechanisms in peacebuilding. .